AN INSTRUCTIVE ALGORITHM FOR AIRCRAFT ELEVATOR SIZING TO BE USED IN PRELIMINARY AIRCRAFT DESIGN SOFTWARE - Al-Shamma, Omran (Journal of Applied Engineering Science, 2017)
The longitudinal control is the essential elevator function. For a safe flight, the aircraft should be longitudinally controllable plus maneuverable. So, it is imperative for the designers to assess the control authority of candidate configurations early in the preliminary design phase. Adding elevator sizing module, as a helpful tool for aeronautical students enhance their knowledge, understanding, and analyzing studies. This paper presents an instructive algorithm for the elevator sizing to be employed in the preliminary aircraft design software. The paper introduced the necessary formulae to guide the designer to achieve the qualifications of the longitudinal control and longitudinal trim. A solved example has been added to explain the application of the algorithm.
Keywords: preliminary aircraft design; control surface design; elevator sizing; elevators; Algorithms